Frontispiece: Bilayer Networks within a Hydrogel Shell: A Robust Chassis for Artificial Cells and a Platform for Membrane Studies. Issue 46 (3rd November 2016) - Baxani, Divesh K.; Morgan, Alex J. L.; Jamieson, William D.; Allender, Christopher J.; Barrow, David A.; Castell, Oliver K.
Abstract : Lipid Bilayers In their Communication onpage 14240 ff., O. K. Castell et al. report droplet networks that are separated by lipid membranes and encapsulated within a semipermeable shell.